Evaluation of brush cytology and DNA image cytometry for the detection of cancer of the oral cavity. Issue 3 (6th January 2016) - Kaur, Manveen; Handa, Uma; Mohan, Harsh; Dass, Arjun
Abstract : Background: Cancer of the oral cavity is the sixth most common malignancy reported worldwide. This study was undertaken to evaluate the efficacy of brush cytology and the adjunctive role of DNA image cytometry (ICM) in the diagnosis of oral cancer. Method: Oral brush smears and biopsy were obtained from 100 consecutive patients presenting with suspicious oral lesions. DNA‐ICM was performed on 96 cytology smears which had adequate cellularity. Results: On cytology, 54 cases were benign, 36 were malignant, 6 were suspicious for malignancy, and 4 were inadequate due to scanty cellularity. On histopathologic examination, 49 cases were diagnosed as squamous cell carcinoma and 51 cases as benign. The sensitivity of brush cytology for the detection of cancer was 83.3% and the specificity was 95.8%. The positive and negative predictive values were 95.2% and 85.2%, respectively, with a diagnostic accuracy of 86%. Out of 96 cases analyzed by image analysis to assess DNA ploidy, 33 cases were aneuploid and 63 were diploid. The sensitivity, specificity, positive predictive value, and negative predictive value of DNA‐ICM were 68.7%, 100%, 100%, and 76.1%, respectively, giving a diagnostic accuracy of 81%. The combination of cytology and DNA cytometry increased the sensitivity to 92% and specificity to 100%. Conclusion: The study demonstrates the usefulness of DNA‐ICM as an adjunct to brush cytology to diagnose oral cancer. It reduces the false negative cases on cytology and also adds to objectivity in cytologically doubtful cases. Diagn. Cytopathol. 2016;44:201–205. © 2016 Wiley Periodicals, Inc.